A shift in follicular fluid from triacylglycerols to membrane lipids is associated with positive pregnancy outcome. Issue 9 (20th June 2019) - Shehadeh, Alaa; Bruck‐Haimson, Reut; Saidemberg, Daniel; Zacharia, Anish; Herzberg, Shmuel; Ben‐Meir, Assaf; Moussaieff, Arieh
ABSTRACT: Follicular fluid (FF) is a liquid that surrounds the ovum. Its metabolite and, specifically, its lipid content have been associated with oocyte development. To characterize possible association between the lipid composition of FF and the outcome of pregnancy, we carried out a lipidomics study and compared the abundance of lipids from FF of patients with positive and negative outcomes. We found a differential lipid network wiring in positive‐outcome FF, with a significant decrease (∼2 fold; P < 0.001) in triacylglycerol levels and higher accumulation (10–50%; P < 0.001) of membrane lipids groups (phospholipids and sphingolipids). In addition to this major metabolic alteration, other lipid groups such as cholesteryl esters showed lower levels in positive‐outcome patients, whereas derivatives of vitamin D were highly accumulated in positive‐outcome FF, supporting previous studies that associate vitamin D levels in FF to pregnancy outcome. Our data also point to specific lipid species with a differential accumulation pattern in positive‐outcome FF that predicted pregnancy in a receiver operating characteristic analysis. Altogether, our results suggest that FF lipid network is associated with the oocyte development, with possible implications in diagnostics and treatment.—Shehadeh, A., Bruck‐Haimson, R., Saidemberg, D., Zacharia. A., Herzberg, S., Ben‐Meir, A., Moussaieff, A. A shift in follicular fluid from triacylglycerols to membrane lipids is associated with positive pregnancy outcome. FASEB J. 33, 10291–10299 (2019). www.fasebj.org